2000
DOI: 10.1086/313902
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Carbapenem-Resistant Acinetobacter Species in Brooklyn, New York: Citywide Prevalence, Interinstitutional Spread, and Relation to Antibiotic Usage

Abstract: Acinetobacter species are problematic nosocomial pathogens. In November 1997, pathogens isolated by microbiology laboratories were collected from 15 hospitals in Brooklyn, New York. Acinetobacter species accounted for 10% of gram-negative isolates. Only half of Acinetobacter species were susceptible to carbapenems; 11 hospitals had at least 1 isolate resistant to carbapenems. Other Acinetobacter susceptibility rates were as follows: polymyxin, 99%; amikacin, 87%; ampicillin/sulbactam, 47%; ceftazidime, 25%; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
1
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(77 citation statements)
references
References 34 publications
3
67
1
5
Order By: Relevance
“…We did not identify an efficient carbapenem-hydrolyzing enzyme (e.g., OXA enzyme or metallo-b-lactamase) in any of the isolates we studied. The finding of increased production of a cephalosporinase in the carbapenem-resistant isolates may explain the persistent relationship we have observed between the rates of carbapenem-resistance and cephalosporin use in individual hospitals in our area [5,17].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We did not identify an efficient carbapenem-hydrolyzing enzyme (e.g., OXA enzyme or metallo-b-lactamase) in any of the isolates we studied. The finding of increased production of a cephalosporinase in the carbapenem-resistant isolates may explain the persistent relationship we have observed between the rates of carbapenem-resistance and cephalosporin use in individual hospitals in our area [5,17].…”
Section: Discussionmentioning
confidence: 73%
“…However, A. baumannii is problematic in hospitals in selected geographic regions [3][4][5]. Approximately 10% of all gram-negative isolates identified in Brooklyn, New York, hospital microbiology laboratories are A. baumannii [5].…”
mentioning
confidence: 99%
“…That is, once A. baumannii is introduced into a hospital, it may persist and become endemic [15,16]. After disseminating throughout our hospital system from the adult ICU, A. baumannii became 1 of the 5 most frequent bacterial pathogens isolated in 2007.…”
Section: Discussionmentioning
confidence: 99%
“…In the year 2010, in India, a study done by Manoharan et al (10) quoted the prevalence of MBLs in P.aeruginosa to be as high as 65 %. In acinetobacter spp, in a study by Manikal et al, (11) in the year 2000 in New York hospitals, the MBLs prevalence was found to be 50%. Later in one Indian study by Taneja et al, in 2003 the prevalence of MBL in acinetobacter was found to be 20%.…”
Section: Discussionmentioning
confidence: 92%